How health capabilities and government restrictions affect the COVID-19 pandemic: Cross-country differences in Europe - Dzúrová, Dagmar; Květoň, Viktor (Applied geography (Sevenoaks, England), 2021)
The COVID-19 pandemic in the first months of 2020 posed an unprecedented threat to the health of the world's population. In this longitudinal design study, we elaborated the typology of 27 European countries based on the complete beginnings of the ongoing COVID-19 pandemic based on health indicators and contextual variables. Two-step analysis using factor scores to run a cluster analysis identifying 5 consistent groups of countries. We then analyze the relationship between the GHS predictive index, the restrictions and health care expenditures within countries categorized into 5 clusters. An analysis of the early stages of a pandemic confirmed that in countries where anti-pandemic measures were rapidly and consistently in place, the spread of the virus was suppressed more rapidly and the first wave of pandemics in these countries was incomparably more benign than in countries with later responses and milder restrictive measures.
Keywords: Suppression and mitigation; GHS predictive Index; European countries; Factory and cluster analyses; Typology; COVID-19 pandemic